Cost and Feasibility Analysis of Copra in Tilamuta District Boalemo Regency - Andi Lelanovita Sardianti; Pristian Zakaria; muhamad yazid bustomi (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Copra is dried coconut flesh and is used as raw material for making crude coconut oil and other derivative products. The aim of this research is to determine the overall costs and feasibility of copra cultivation in Mohungo Village, Tilamuta District, Boalemo Regency. This research uses quantitative techniques, such as feasibility and cost analysis. By using the Slovin formula (20%), the research sample used in this study consisted of 20 respondents. The results of this research explain that (1) The coconut copra business in Mohungo Village, Tilamuta District, Boalemo Regency incurs total costs of Rp. 13,331,000,- or an average of IDR 666,550,-. (2) After deducting variable costs and fixed costs, the average income from the copra business in Mohungo Village, Tilamuta District, Boalemo Regency is IDR 87,642,200. or an average of Rp. 4,382,110,- (3) Feasibility of the copra business, namely revenue to costs (R/C) ratio of 7.57, meaning for every Rp. 100,000,- costs incurred, the copra business provides revenue of Rp. 757,000,-. The R/C ratio acceptance figure of 7.57 shows that this copra is worth cultivating.